Comparative Toxic Effects of Methamidophos and Cypermethrin on Cholinesterase Enzyme of Callosobruchus analis - Nighat Gul,; M. Farhanullah Khan,; Afaq Ahmad Siddiqui ,; M. Arshad Azmi, (Journal of Basic & Applied Sciences, 2012)
In the present study the cholinesterase inhibition was observed as 65% and 12, for methamidophos and cypermethrin,respectively. LC50 values were found as 16 and 2.2, g/cm2 for methamidophos, cypermethrin, respectively against Callosobruchus analis by the filter paper impregnation method after 24 hours of treatment. The order of efficacy was found as cypermethrin >methamidophos.